Redefining Medieval Balaghah Epistemology: Theoretical Transformations In The Syarah and Hasyiyah Traditions - Aang Saeful Milah; Sulistiani Sulistiani; Uum Umaroh Husaeni; Mugiroh Mugiroh; Insan Ramadhan (Nurul Jadid University, 2026)
This study reconstructs the epistemology of medieval Balaghah. Its aim is to deconstruct the Western-centric narrative that labels the era of commentary (commentary tradition) as a phase of intellectual decline (‘ashr al-inhithath). Specifically, this study maps the theoretical transformations in three branches of Balaghah resulting from the integration of formal logic (manthiq). The method used is qualitative with a historical-philosophical approach. The researcher applies Michel Foucault’s theory of the archaeology of knowledge to analyze the corpus of primary texts (turats), ranging from the works of Al-Sakkaki (d. 626 AH), Al-Qazwini (d. 739 AH), to the authoritative commentaries by Al-Taftazani (d. 793 AH) and Al-Jurjani al-Syarif (d. 816 AH). Analysis of six cross-cluster cases reveals a robust conceptual refinement. The Syarah and Hasyiyah traditions are shown to operate as independent internal critical ecosystems through the